Challenges and Opportunities in Remote Prototyping: A Case-Study during COVID-1. (May 2022) - Martins Pacheco, N. M.; Vazhapilli Sureshbabu, A.; Dieckmann, E.; Apud Bell, M.; Green, S.; Childs, P.; Zimmermann, M.
Abstract: Collaboration is common practice within design disciplines and beyond. Brainstorming, discussions, and prototyping tend to occur within the same physical space. The reduction of human interaction during the COVID-19 pandemic disrupted these practices. In this paper, we focus on the possibilities and challenges of remote prototyping of four student teams by combining a double diamond approach with tools to overcome remote work challenges. The results were analyzed to understand crucial tools, advantages, and obstacles. The key challenges and opportunities were then identified and examined.